Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Get quick and reliable solutions to your questions from a community of experienced professionals on our platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

Convert the equation to logarithmic form: e =A) ln(m) = sB) ln(S) = mO In(e) = sD) In(e) = m

Convert The Equation To Logarithmic Form E A Lnm SB LnS MO Ine SD Ine M class=

Sagot :

The given equation is:

[tex]e^m=s[/tex]

Take the natural log of both sides:

[tex]\ln e^m=\ln s[/tex]

Apply the power rule of logarithms:

[tex]\begin{gathered} m\ln e=\ln s \\ Also\text{ }\ln e=1,\text{ then} \\ m*1=\ln s \\ m=\ln s \\ \text{ Reorder terms} \\ \ln(s)=m \end{gathered}[/tex]

The answer is B. ln(s)=m